Elongation Factor Tu and DnaK Are Transferred from the Cytoplasm to the Periplasm of Escherichia coli during Osmotic Downshock Presumably via the Mechanosensitive Channel MscL - Berrier, Catherine (American Society for Microbiology, 2000)
Upon osmotic downshock, a few cytoplasmic proteins, including thioredoxin, elongation factor Tu (EF-Tu), and DnaK, are released from Tris-EDTA-treated Escherichia coli cells by an unknown mechanism. We have shown previously that deletion of mscL, the gene coding for the mechanosensitive channel of the plasma membrane with the highest conductance, prevents the release of thioredoxin. We confirm and extend the implication of MscL in this process by showing that the release of EF-Tu and DnaK is severely impaired in MscL-deficient strains. Release of these proteins is not observed in the absence of a Tris-EDTA treatment which disrupts the outer membrane, indicating that, in intact cells, they are transferred to the periplasm upon shock, presumably through the MscL channel.